A Performance Test for Assessment of Long-Term Creep Behavior of Soil-Geosynthetic Composites. Issue 1 (1st January 1996) - Wu, J.T.H.; Helwany, S.M.B.
Abstract : A simple laboratory performance test was devised for the assessment of long-term creep behavior of geosynthetic reinforcement due to soil-geosynthetic interaction. In the test, the geosynthetic reinforcement and the confining soil deformed in an interactive manner under a sustained surcharge that was applied to the soil over a long period of time. Two long-term performance tests were conducted with different confining soils: a clean sand, and a kaolin clay. The tests clearly indicate that the long-term creep deformation of the geotextile reinforcement was significantly affected by the time-dependent deformation characteristics of the confining soils. It can be misleading to evaluate the long-term creep potential of a soil-geosynthetic composite based solely on the results of geosynthetic element creep tests such as constant load strip tensile tests and, confined creep tests which do not account for time-dependent deformation of the confining soil.